Ukraine Unified Transport System Potential and Its Development Management Effectiveness Integral Assessment - Olha, Komelina; Viktor, Dubishchev; Mykola, Lysenko; Nataliia, Panasenko (International Journal of Engineering and Technology, 2018)
Transport system is an important constituent of country’s economy. This system development is a significant factor ensuring population standard of living. Research in the field of unified transport system of Ukraine development estimates reveals its condition as not sufficient to meet modern requirements.    Among the problems which are to be first of all solved to improve transport system of Ukraine operation estimates, an important place belongs to the issues of industry management information and analytical provision:  lack of data collecting and processing effective system, methodology for objective condition assessment and prospective of the industry development, systematic approach to development coordination and long-term panning of all modes of transport operation, criteria and indices for quality estimation in providing transportation services. Solving these problems is impossible without significant improving the country’s unified transport system management. Transport infrastructure in Ukraine requires considerable systemic changes, oriented to logistics which will provide integration effect, reduce costs and improve service quality.    Methodology for the national economy transport system development integral estimation was developed based on the modern information base including approach to determining peculiarities of forming transport system of Ukraine potential and its development management effectiveness under global challenges. The developed methodical approach can be efficiently used for analyses, control, accounting, planning, forecasting and regulating the industry activity at the national and regional levels and the level of separate country’s transport subsystems. Suggested approach can be used for evaluating efficiency of transport system development innovative and investment projects, and is the basis for defining market transformation vectors considering its socially optimal development level as well as regarding innovative and investment projects financing.